Mario Krešić, In Search of the Functions of the Legal System: Axiomatic and Methodological Stages (W poszukiwaniu funkcji systemu prawnego: etapy aksjomatyczne i metodologiczne) - Dąbrowski, Karol (Studia Prawa Publicznego, 2025)
Mario Krešić, In Search of the Functions of the Legal System: Axiomatic and Methodological Stages (W poszukiwaniu funkcji systemu prawnego: etapy aksjomatyczne i metodologiczne), „Acta Universitatis Carolinae – Iuridica” 2024, vol. 70, no. 4, s. 11–30, https://doi.org/10.14712/23366478.2024.157